The effect of relationship marketing towards switching barrier, customer satisfaction, and customer trust on bank customers - Kadarisman Hidayat; Muhammad Ishlah Idrus (Journal of Innovation and Entrepreneurship, 2023)
Basically, relationship marketing focuses more on creating customer value through interaction with customers to get information regarding evaluation of customer needs and expectations on an ongoing basis. Interaction with customers must be conducted, because customer involvement can increase customer value, so that the company can meet their expectations and needs. Furthermore, customer satisfaction, customer trust, and customer retention can be influenced by the implementation of a relationship marketing strategy. This study aims to examine and analyze the correlation between relationship marketing variables to switching barriers, customer satisfaction, customer trust and customer retention. Regarding to the objectives and study hypotheses, structural equation technique (SEM) is considered as relevant to be used. The population in this study was BNI customers who are members of BNI Emerald in East Java Province. The sample was obtained based on the top five BNI branches. Furthermore, the sample was determined by area proportional random sampling based on branches with a total sample of 141 respondents. Based on the study results, it is concluded that the effect of Relationship Marketing on Switching Barriers, Customer Satisfaction, and Customer Trust is positively significant. As a result, relational marketing is positioned as the primary exogenous variable to be investigated in conjunction with other relevant factors, such as switching barrier variables, customer happiness, customer trust, and customer retention. Customer satisfaction has a considerable positive impact on customer trust, indicating that the better the customer satisfaction, the higher the customer trust. Customer satisfaction has a positive and considerable impact on customer retention, indicating that the better the customer satisfaction, the higher the customer retention.
Keywords: 650; Customer retention; Customer satisfaction; Relationship marketing; SEM (structural equation modelling); Switching barrier